2021
DOI: 10.3390/ph14080747
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Culture of Rosmarinus officinalis L. in a Temporary Immersion System: Influence of Two Phytohormones on Plant Growth and Carnosol Production

Abstract: Emerging infectious diseases have become a major global problem with public health and economic consequences. It is an urgent need to develop new anti-infective therapies. The natural diterpene carnosol exhibit a wide variety of interesting antibacterial and antiviral properties, and it is considered a theoretical inhibitor of COVID-19 Mpro. However, this compound is present in the family Lamiaceae in low quantities. To obtain carnosol in concentrations high enough to develop pharmacological studies, we evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…5 B, C). So far, bioreactor cultivation of sage in vitro shoots has been scarcely studied 51 , 52 .
Figure 6 Growth parameters (dry weight – DW and growth index—Gi) of S. apiana microshoots, maintained in different bioreactors, during 7–42 days of cultivation.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 B, C). So far, bioreactor cultivation of sage in vitro shoots has been scarcely studied 51 , 52 .
Figure 6 Growth parameters (dry weight – DW and growth index—Gi) of S. apiana microshoots, maintained in different bioreactors, during 7–42 days of cultivation.
…”
Section: Resultsmentioning
confidence: 99%
“…However, research demonstrated that a temporary immersion system is effective for cultivating in vitro shoots of S. rosmarinus 52 . In the current work, the concentrations of the major constituents of S. apiana essential oil varied depending on the bioreactor type.…”
Section: Resultsmentioning
confidence: 99%
“…In our research, we used a 1min immersion time with a 1h interval to achieve short but frequent contact of the explant with the medium. Perez et al [ 27 ] found that immersion for 1 min every 4 h induced 114 cotyledonary embryos in Quercus suber , which was significantly more than the 48 embryos obtained with immersion for 1 min every 6 h and the 14 embryos obtained with immersion for 1 min every 12 h. Similarly, Villegas-Sanchez et al [ 47 ] demonstrated that more frequent immersion of Rosmarinus officinalis explants leads to excellent results. Immersion for 1 min every 12 h resulted in 170 new shoots, while immersion for 1 min every 24 h produced only three new shoots.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have shown that TIS have numerous advantages as regards the semi-solid methods (Vidal and Sánchez, 2019 ). These systems have been successfully used for micropropagation of Stevia rebaudiana (Melviana et al, 2021 ), Colocasia esculenta L. Schott (Mancilla-Álvarez et al, 2021 ), Agave angustifolia (Monja-Mio et al, 2021 ), Rosmarinus officinalis L. (Villegas-Sánchez et al, 2021 ), Dracocephalum forrestii (Weremczuk-Jezyna et al, 2020 ), Guarianthe skinneri (Leyva-Ovalle et al, 2020 ), and the number is increasing steadily. In our laboratory, we have developed protocols using bioreactor propagation systems with liquid medium for axillary shoots of chestnut, alder and willow (Vidal et al, 2015 ; Cuenca et al, 2017 ; Regueira et al, 2018 ; San José et al, 2020 ; Gago et al, 2021 ), and somatic embryos of Quercus robur (Mallón et al, 2012 , 2013 ).…”
Section: Introductionmentioning
confidence: 99%